Is Dupilumab a chance for patients with moderate to severe atopic dermatitis? Literature review - Iwańczuk, Paweł (Journal of Education, Health and Sport, 2024)
Introduction: Atopic dermatitis is an inflammatory disease which can significantly affect quality of life of patients. Especially severe forms of this disease are challenging to treat and for a long time forms of treatment have been limited. Because of that- it is crucial to find new ways of treatment which can be registered and impove moderate and severe dermatitis. Aim of study: Fundament purpose of this literature review is focusing on effectiveness, safety, side effects or different potential medical applications of Dupilumab. The main question, which is formulated in the title- is Dupilumab a chance for patients with moderate to severe atopic dermatitis? State of knowledge: Nowadays Dupilumab is well known drug and a lot of trials and analysis focus on efficacy, safety in treatment of moderate and severe dermatitis. The development of Dupilumab and different potential, clinical applications is also a chance for other groups of patients- for example patients with asthma, chronic rhinosinusitis with nasal polyps, eosinophilic esophagitis, prurigo nodularis. Conclusion: Dupilumab is definitely a relevant and essential element of treatment therapy for patients with moderate to severe atopic dermatitis. There were many analysis and researches which confirmed effectiveness, safety level and described Dupilumab impact on many different parameteres and scales focused on symptoms and life quality of patients during treatment with Dupilumab.